HUBUNGAN PERILAKU BELAJAR DENGAN KEJADIAN MIOPIA (RABUN JAUH) - Lenawati, Helena; Rudi, Eka (Akademi Keperawatan Pamenang, 2012)
In youth generation or student, myopia is problem of eyeâs health that are still often experiencedÂ until now. Beside the genetic factors, study behavior is often linked to the prevalence of myopia among students. The purpose of this research is to know whether there is any relation of study behavior with the incidence of myopia.The research design used in this research is analytic cross sectional. Its population is all the first-level students of Pamenang Nursery Academic Pare, while the samples in this research were several students of the first student amount to 55 students. The data was collected use instrument of questionnaire and secondary data of eyes examination results. Data analysis was conducted by using test of Contingency Coefficient.Research Results showed that there are at least 7 students (12.7%) who have study behavior that less good experiencing myopia.While the data analysis showed result of correlation 0.707 with Ï = 0.000 and Î± = 0.05 so found Ï < Î± then the H1 is accepted. And it can be concluded there is a positive relation between study behavior and the occurrence of myopia.From these results researcher suggest students in order to pay attention and maintain the eyesâ health by implement good study behavior, so can reduce the risk to experience the events of myopia.Â Â Keywords : Behavior, Study, Myopia